Yellow Nail Syndrome- A Case Report - Chowdhury, NH; Selim, S; Yasmin, R; Rowshan, AHM; Rahman, MR (Journal of Bangladesh College of Physicians and Surgeons, 2010)
Yellow nail syndrome (YNS) is a rare disorder characterized by chronic/recurrent rhinosinusitis, pleural effusion, bronchiectasis, lymphedema and dystrophic yellow nails. The classic triad of lymphedema, slow growing yellow nails, and pleural effusion, described by Emerson, is seen in only one third of patients. Here we report a case of yellow nail syndrome presented with cough, worsening symptom of breathlessness, leg edema and nail changes, waxing and waning for about 17 years. Key words: Yellow nail; lymphedema; pleural effusion; maxillary sinusitis. DOI: 10.3329/jbcps.v28i1.4645 J Bangladesh Coll Phys Surg 2010; 28: 49-52